Records Transfer from Central Files to the Records Center: A Case Study at the National Library of the Republic of Indonesia - Dewi, Ratna Candra; Aulianto, Dwi Ridho; Rachmaningsih, Dewi Maharani (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
This study investigates the procedures involved in the transfer of inactive archives at the National Library of the Republic of Indonesia. The data were collected through direct observation and semi-structured interviews with relevant personnel. The findings revealed that the process of transferring inactive archives comprises several key stages: the initial selection and appraisal of records, the compilation and verification of archival data within the processing unit, the preparation of transfer documentation through official minutes, and the physical or digital transfer of archives to the archival unit. The study underscores the importance of adhering to established procedures to ensure accountability, traceability, and compliance with institutional archival policies. These findings contribute to a better understanding of archival lifecycle management practices within national-level institutions and highlight the need for standardized workflows to facilitate efficient and legally sound archival transfers.